Video-assisted thoracic surgery (VATS) hybrid esophagectomy after neoadjuvant treatment – case report - Vela Ilir; Igor Dzikovski; Despot Despotovski; Faik Misimi; Marija Simonovska; Asaf Abdurahmani; Irfan Ismaili (My University, 2023)
Esophageal cancer is an aggressive malignancy. It is 6 th among the leading causes of cancer death and the 8 th most common cancer type worldwide. Regarding gender distribution, esophageal cancer is about 2–4 times more frequent among males than females. There are two main histological types; esophageal squamous cell carcinoma is typically localized in the upper- middle esophagus being the most frequent histological type and adenocarcinoma subtype, usually localized in the lower esophagus. Over the past two decades, video-assisted thoracic surgery (VATS) has revolutionized how thoracic surgeons diagnose and treat esophageal diseases. Because of the advancement of surgical laparoscopic and thoracoscopic procedures and endoscopic instrumentation, minimally invasive esophagectomy (MIE) is performed to enhance surgical outcomes and reduce surgical morbidity. Here, we present a case of, video-assisted thoracic surgery hybrid esophagectomy in a 63-year-old patient with esophageal cancer who had received neoadjuvant therapy. Surgical technique: the patient was first placed in the supine position under general anesthesia and double-lumen intubation. An upper median laparotomy was performed to mobilize and tubulate the stomach conduit. Then we continued with a left lateral decubitus position; 4 cm incision was made in the 5th intercostal space to accommodate the thoracoscopic instruments. The dissection and mobilization of the esophagus were carried out from the esophageal hiatus to the upper thoracic inlet after opening the posterior mediastinal pleura. After this step, the stomach conduit was pulled-up through the esophageal hiatus and laterolateral esophagogastric anastomosis was done in the chest. The postoperative course ended without complications, and the patient was discharged home on the 5th postoperative day. The, video-assisted thoracic surgery hybrid approach is an excellent option for esophageal cancer management, offering a quick recovery and low morbidity.
Keywords: video-assisted thoracic surgery (VATS); minimally invasive esophagectomy; Ivor Lewis esophagectomy; esophageal cancer